2020
DOI: 10.3390/ijms21218044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quercetin 3-O-β-D-Galactopyranoside on the Adipogenic and Osteoblastogenic Differentiation of Human Bone Marrow-Derived Mesenchymal Stromal Cells

Abstract: Natural products, especially phenols, are promising therapeutic agents with beneficial effects against aging-related complications such as osteoporosis. This study aimed to investigate the effect of quercetin 3-O-β-D-galactopyranoside (Q3G), a glycoside of a common bioactive phytochemical quercetin, on osteogenic and adipogenic differentiation of human bone marrow-derived mesenchymal stromal cells (hBM-MSCs). hBM-MSCs were induced to differentiate into osteoblasts and adipocytes in the presence or absence of Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
(42 reference statements)
0
14
0
1
Order By: Relevance
“…Quercetin is one of the natural polyphenols, which widely exists in various plants and was consumed worldwide(18). It has multiple pharmacological effects reported by many studies, such as protecting the bone, reduceing blood glucose, blood pressure, and lipid, and immunomodulatory, anti-in ammatory, and antioxidation activities (19)(20)(21). Wogonin, a compound extracted from the Scutellaria baicalensis plant, exhibits high anti-in ammatory and antioxidative properties, which is achieved reduce expression of transforming growth factor β1 (TGF-β1), high temperature receptor A1 (HTRA1), matrix metalloprotease 13 (MMP-13) and nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB) (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is one of the natural polyphenols, which widely exists in various plants and was consumed worldwide(18). It has multiple pharmacological effects reported by many studies, such as protecting the bone, reduceing blood glucose, blood pressure, and lipid, and immunomodulatory, anti-in ammatory, and antioxidation activities (19)(20)(21). Wogonin, a compound extracted from the Scutellaria baicalensis plant, exhibits high anti-in ammatory and antioxidative properties, which is achieved reduce expression of transforming growth factor β1 (TGF-β1), high temperature receptor A1 (HTRA1), matrix metalloprotease 13 (MMP-13) and nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB) (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that cyanidin promoted adiponectin expression in 3T3-L1 cells (Matsukawa et al, 2015) and exhibited a protective effect against palmitic acidinduced hypertrophy via PI3K/Akt signaling in 3T3-L1 adipocytes (Molonia et al, 2020). Quercetin is known to suppress adipogenesis in 3T3-L1 cells and MSCs by regulating the AMPK and mitogenactivated protein kinase signaling pathways (Ahn et al, 2008;Oh et al, 2020). Caffeic acid is known to decrease the adipogenesis of 3T3-L1 cells via the induction of AMPK signaling activation (Eid et al, 2017).…”
Section: Differentiation Of Adipocytes Is Tightly Regulated Viamentioning
confidence: 98%
“…Further studies demonstrated that Nestin + MSCs isolated from PTH-treated mice displays enhanced proliferation and differentiation into osteoblasts in culture ( Méndez-Ferrer et al, 2010 ; Ding et al, 2012 ); as well as increased osteogenic differentiation capacity in vivo ( Fan et al, 2017 ). Other studies based on drug screening of natural senolytic substances such as Celastrol and Quercetin 3-O-β-D-galactopyranoside was also shown to promote osteogenesis and inhibit adipogenesis in vitro through PGC-1α signaling ( Li et al, 2020 ; Oh et al, 2020 ). On a similar note, inhibition of the mTOR-pathway was shown to extensively prolong life-span in mice ( Papadopoli et al, 2019 ), including revitalized pluripotency of human MSCs in vitro ( Antonioli et al, 2019 ).…”
Section: Msc Changes In Aging Bone Marrowmentioning
confidence: 99%